Analysis the Effect of Flux and Water Characteristics on Polyethersulfone Ultrafiltration Membrane Performance as Pre-Treatment of SWRO - Sucipta Laksono; Irwan Irwan; Sandyanto Adityosulindro (Jurnal Ilmu Lingkungan, 2024)
Increasing human population resulted in higher demand for potable freshwater, while freshwater sources were limited. As an alternative solution, seawater was necessarily to be employed as a main source of water supply and necessarily treated with Seawater Reverse Osmosis (SWRO). However, membrane fouling of SWRO was occurred. Therefore, implementation of ultrafiltration membranes as pre-treatment were necessary. In this study, identification of removal efficiency seawater characteristics of TDS, COD, conductivity, and UV-Vis parameters at different flux and investigation of the fouling rate at variations filtration performance of the 50 kDa MWCO pore size PES ultrafiltration membrane was performed. Filtration of laboratory scale experiment with constant flux of 120 L/m²⋅h and 180 L/m²⋅h at dead-end operation was performed. Filtration of 50 kDa PES ultrafiltration membrane was able to remove effectively turbidity, TDS, UV-Vis, conductivity, and COD with 63±6%; 37±19%; 7±4%; 33±33%; dan 97.86%, respectively. Furthermore, related to membrane performance, filtration at 120 L/m²·h flux operation was found as the common fouling mechanisms, while flux operation at 180 L/m²·h resulted different behavior resulted for severe membrane performance.  The suitable operation of fluxes 120 L/m²·h was recommended to increase the performance and membrane lifespan as well as to decrease the load of SWRO unit.